TINGKAT KETERAMPILAN PASSING-STOPING DALAMPERMAINAN SEPAKBOLA PADA MAHASISWA PJKR BANGKATAN 2013 - Nurhadi Santoso (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2014)
AbstractKnown in the implementation of learning the game of football a lot of students in doing the passing-stopping encountererrors. In this study conducted for the purpose of knowing the skill level of students passing-stopping PJKR B force2013 in playing football. This research is a descriptive study. Subjects in the study were students PJKR B force in2013 that took the eye of Association Football Motion totaling 42 students. Instruments used test-stopping passing ofNurhasan that have been modified. The validity of this instrument of 0.64, while the reliability of 0.96. Data analysistechniques using descriptive statistics. The results showed that male students have the skill level of the passingstoppingin either category there are 5 students (18.52%), moderate category there are 17 students (62.96%), andless category there are 5 students (18.52%). While the results for students passing-stopping daughter in eithercategory there are 3 female students (20%), moderate category there are nine female students (60%), and lesscategory there are 3 female students (20%).Keywords: Skills, Passing-stopping.AbstrakDiketahui dalam pelaksanaan pembelajaran permainan sepakbola banyak mahasiswa dalam melakukan passingstoppingmengalami kesalahan. Dalam penelitian ini dilakukan untuk tujuan mengetahui tingkat keterampilanpassing-stopping mahasiswa PJKR B angkatan 2013 dalam bermain sepakbola. Jenis penelitian ini adalah penelitiandeskriptif. Subjek dalam penelitian adalah mahasiswa PJKR B angkatan 2013 yang mengambil mata Dasar GerakSepakbola yang berjumlah 42 mahasiswa. Instrumen yang digunakan tes passing-stopping dari Nurhasan yang telahdimodifikasi. Adapun validitas instrumen ini sebesar 0,64 sedangkan reliabilitas sebesar 0,96. Teknik analisis datanyamengunakan statistik deskriptif. Hasil penelitian menunjukkan mahasiswa putra yang memiliki tingkat keterampilanpassing-stopping dalam kategori baik ada 5 mahasiswa (18,52%), kategori sedang ada 17 mahasiswa (62,96%),dan kategori kurang ada 5 mahasiswa (18,52%). Sedangkan hasil penelitian passing-stopping untuk mahasiswaputri dalam kategori baik ada 3 mahasiswi (20%), kategori sedang ada 9 mahasiswi (60%), dan kategori kurangada 3 mahasiswi (20%).Kata Kunci: Keterampilan, Passing-stopping.